AKTIVITAS ANTIBAKTERI BUNGA KERTAS (Bougainvillea glabra): REVIEW ARTIKEL - Supratman, Rafif Ghanaifalah Dely; Hairani, Rita; Ruga, Ritbey (PROSIDING SEMINAR KIMIA, 2025)
Herbal or medicinal plants contain many diverse phytochemical compounds and provide various biological effects. One of them is Bougainvillea glabra which is often used in traditional medicine in various countries due to the plant has bioactive compounds, one of which is antibacterial. This study aims to determine the antibacterial activity of Bougainvillea glabra. The methodology used was a literature study using several scientific articles about antibacterial activity published in the last ten years and published in national and international scientific journals as library sources through searches on Google Scholar site. The results showed that Bougainvillea glabra had inhibitory activity against the bacteria Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Bacillus cereus, but it had not inhibitory activity against the bacteria Listeria monocytogenes and Salmonella sp. Keywords : Bougainvillea glabra, bioactive, antibacterial